2020
DOI: 10.1021/acs.inorgchem.0c00428
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable Phosphor KBa2(PO3)5:Eu2+ with Broad-Band Cyan Emission Caused by Multisite Occupancy of Eu2+

Abstract: The relationship between the structure and properties is always a hot topic in the luminescent material field. In this work, a new phosphor KBa 2 (PO 3 ) 5 :Eu 2+ (KBP:Eu) was prepared by a high-temperature solid-state reaction method and characterized by X-ray diffraction, energy-dispersive X-ray spectroscopy, photoluminescence (PL), and electroluminescence studies. The polyphosphate host KBP offers three lattice environments (K1, Ba1, and Ba2) for Eu 2+ ions to realize broad-band emission from 380 to 700 nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Compared with other Eu 2+ doped blue phosphors, the Ea of CBH : Eu 2+ is higher than those of Ba 3 Si 6 O 12 N 2 : Eu 2+ ( Ea =0.24 eV), [72] RbNa(Li 3 SiO 4 ) 2 : Eu 2+ ( Ea= 0.25 eV), [73] K 2 YZr(PO 4 ) 3 : Eu 2+ ( Ea= 0.25 eV), [68] Ba 3 CaK(PO 4 ) 3 : Eu 2+ ( Ea= 0.26 eV ), [70] K 2 Al 2 B 2 O 7 : Eu 2+ ( Ea =0.30 eV) [74] . But the Ea of CBH : Eu 2+ is lower than that of Sr 5 SiO 4 Cl 6 : Eu 2+ ( Ea =0.35 eV), [75] K 2 BaCa(PO 4 ) 2 : Eu 2+ ( Ea =0.51 eV), [76] and KBa 2 (PO 3 ) 5 : Eu 2+ ( Ea= 0.66 eV) [77] . The relatively high activation energy indicates that the phosphor has good thermal stability, which is an essential condition for practical applications.…”
Section: Resultsmentioning
confidence: 96%
“…Compared with other Eu 2+ doped blue phosphors, the Ea of CBH : Eu 2+ is higher than those of Ba 3 Si 6 O 12 N 2 : Eu 2+ ( Ea =0.24 eV), [72] RbNa(Li 3 SiO 4 ) 2 : Eu 2+ ( Ea= 0.25 eV), [73] K 2 YZr(PO 4 ) 3 : Eu 2+ ( Ea= 0.25 eV), [68] Ba 3 CaK(PO 4 ) 3 : Eu 2+ ( Ea= 0.26 eV ), [70] K 2 Al 2 B 2 O 7 : Eu 2+ ( Ea =0.30 eV) [74] . But the Ea of CBH : Eu 2+ is lower than that of Sr 5 SiO 4 Cl 6 : Eu 2+ ( Ea =0.35 eV), [75] K 2 BaCa(PO 4 ) 2 : Eu 2+ ( Ea =0.51 eV), [76] and KBa 2 (PO 3 ) 5 : Eu 2+ ( Ea= 0.66 eV) [77] . The relatively high activation energy indicates that the phosphor has good thermal stability, which is an essential condition for practical applications.…”
Section: Resultsmentioning
confidence: 96%
“…23 where E and Q represent the energy positions of the 5d-band edge of the doped Eu 2+ ions (cm −1 ) and the lower 5d-band of free Eu 2+ ions (34 000 cm −1 ), respectively; V is the valence of the Eu 2+ ion ( V = 2); n is the coordination number of the doped Eu 2+ ion (7 or 9); E a is the electron affinity of the anions (it is a constant for the same host, eV); r is the radius of the cation replaced with Eu 2+ ions (Å). 24 The local structure of the BLOS lattice is complex, so it is difficult to accurately obtain the exact energy level of Eu 2+ at a specific site. 8 However, according to eqn (5), it can be found that the value of E is proportional to r and n quantities.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, two different crystal field strengths are formed, as well as two different red shift degrees. Van Uitert proposed that the red shift degree brought by the crystal field might be evaluated by eq : , Here, E and Q (34000 cm –1 ) means the doped and free Eu 2+ 5d energy level positions, respectively; V is the charge number of 2; n is the coordination number of doped Eu 2+ (12 or 9); E a stands for a constant of 2.0 eV herein; r is the radius of K + ion substituted by an activator . By the values were plugged in, the following results were obtained: E K(1) = 23230 cm –1 (430 nm) and E K(2) = 26256 cm –1 (381 nm).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, two different crystal field strengths are formed, as well as two different red shift degrees. Van Uitert proposed that the red shift degree brought by the crystal field might be evaluated by eq 6: 44,45…”
Section: ■ Results and Discussionmentioning
confidence: 99%